Nutritional Surveillance in Head and Neck Cancer Patients during Radiotherapy —the Difference between Concurrent Chemoradiotherapy using High-dose Cisplatin and Radiotherapy alone - Nishiyama, Kinji; Yoshino, Kunitoshi; Uemura, Hirokazu; Fujii, Takashi; Nakahara, Susumu; Suzuki, Motoyuki; Inohara, Hidenori (Nippon Jibi Inkoka Gakkai Kaiho, 2012)
Concurrent chemoradiotherapy (CCRT) has been widely used in organ preservation for advanced head and neck squamous cell carcinoma. Malnutrition, one of the most detrimental side effects concerned with CCRT, occurs frequently in patients with CCRT, but few studies have reported on the nutritional status in detail during CCRT. The aim of this study was to evaluate the changes in the nutritional status during CCRT compared with radiotherapy alone (RT). We introduce hypopharyngeal cancer patients as the subjects that include 26 cases who underwent CCRT with high dose cisplatin (80mg/m2×3: goal 240mg/m2 in total) and also 26 cases who underwent RT during the same period. For evaluation, we examined the rate of body weight change, serum albumin, total lymphocyte counts and hemoglobin. In this context, the rate of body weight change is the most reliable indicator, and the rate of change at the end of treatment as compared to before the start of treatment was 3.8% in patients treated with RT and 8.1% in patients treated with CCRT. This result suggests that improvement in nutritional status is necessary when considering patients undergoing CCRT. However, regarding completion of treatment, when radiotherapy was not interrupted due to adverse events the median total dose of cisplatin of 240 mg/m2 seemed satisfactory. In addition, regarding the route for energy intake, tube feeding was required only in 2 patients (7.7%) in the RT group and 4 patients (15.4%) in the CCRT group, and no significant difference was found between them. Therefore, percutaneous endoscopic gastrostomy (PEG) for CCRT in advance would be unnecessary at least for hypopharyngeal cancer patients.